DESKRIPSI KEMIMPINAN DAN PELATIHAN KERJA TERHADAP KINERJA ORGANISASI PT. TRANS OTO INTERNASIONAL - Bongsu Saragih (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
A leader in an organization must have the ability to control or influence others. Other factors are expected to encourage the performance of each individual employee, namely job training. This study aims to find out how the description and conditions of leadership and job training influence organizational performance of PT. Trans Oto International both simultaneously and partially. Research samples were 50 respondents. The analysis technique uses multiple regression analysis. The analysis shows that leadership and training simultaneously affect organizational performance. This shows that leadership plays a role in improving organizational performance and better employee training can lead to higher organizational performance. Leadership partially affects organizational performance, which means that implementing better leadership in the company can improve organizational performance. Training partially affects organizational performance, which means that the better the training that employees follow can improve organizational performance.